CONSTRUCTIVE CRITICISM OF ULUM AL-QURAN, HADITH STUDIES, AND ISLAMIC JURISPRUDENCE FROM A CONTEMPORARY SCIENTIFIC PERSPECTIVE - Maltifal; Aljamaedi; Yanfaunnas; Muksinin, Muksinin; Syahruddin (Journal International Dakwah and Communication, 2026)
Classical Islamic sciences face global challenges in maintaining their relevance and epistemological authority amidst the development of modern scientific methodologies that emphasize historical criticism, interdisciplinary analysis, and responsiveness to contemporary issues. This article argues that apologetic or defensive approaches are no longer adequate, and that constructive criticism based on contemporary scientific frameworks is an intellectual necessity. The research objectives are threefold: 1) to map the points of dialogue and tension between classical epistemology and modern methods; 2) to offer constructive criticism to strengthen the validity of these sciences; and 3) to propose an integrative framework for responsible revitalization. To achieve these goals, this study employs a qualitative-interdisciplinary method through a systematic critical-analytical literature study, involving internal textual analysis, critical dialogue with hermeneutics, sociology of knowledge, and applied ethics, as well as normative synthesis. The results map the key dialectics and propose a model of "Revitalized Naql-'Aql-Maqashid Epistemology," where textual authority is creatively dialogued with enriched critical reasoning and directed by the universal objectives of Sharia (Maqashid al-Shari'ah) as an integrative compass. The contribution of this research lies in a critical synthesis that avoids both fundamentalism and ungrounded liberalism. The primary limitation of this study is its conceptual and textual nature, thus requiring further testing and operationalization through empirical case studies and direct engagement with religious practitioner communities to test the application and impact of the proposed framework.